Specific structural changes in Parkinson’s disease-related olfactory dysfunction compared to others forms of olfactory dysfunction - Brosse, Sarah; Tremblay, Cécilia; Mérida, Inés; Frasnelli, Johannes (Frontiers in Neural Circuits, 2024)
Context Olfactory dysfunction (OD) is a common early symptom of Parkinson’s disease (PD). However, OD is not specific to PD, as approximatively 20% of the general population exhibit different forms of OD. To use olfactory measures for early Parkinson screening, it is crucial to distinguish PD-related OD from Non-Parkinsonian OD (NPOD). Objectives and hypothesis This study aimed to compare the structural changes associated with PD-related OD (n = 15) with NPOD (n = 15), focusing on gray matter volumes and white matter fiber integrity in chemosensory regions. We hypothesized that PD-related OD presents specific structural alterations in these regions. Methods Participants underwent a 3 T MRI scan, which included anatomical T1 and diffusion-weighted imaging. Gray and white matter integrity were assessed using both whole-brain analyses (voxel-based morphometry—VBM and tract-based spatial statistics—TBSS, respectively) and localized approaches, including regions of interest and tractography. Results PD patients exhibited significantly higher gray matter volume in the left insula using restricted regions-of-interest analyses, while no other significant gray or white matter differences were found between groups. Conclusion Structural imaging of the gray matter, particularly the insula, but not of white matter, differentiates PD-related OD from NPOD.